Interculturalidade e sustentabilidade: jogos e brincadeiras indígenas na Educação Física escolar - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
In the process of education and intergenerational transmission of culture, games, toys and games appear as important instruments, providing individuals with their own characteristics, perpetuating culture, ways of life and strengthening identities. But most of these games and jokes that enchant are disappearing. Specifically, indigenous games, toys and games inherited by traditional peoples, as is the case with indigenous peoples, are little explored and often made invisible in the practice of School Physical Education and are thus being lost in time and space. Thus, the objective of this research was to rescue games, toys and indigenous games from ethnic groups of the Rio Negro in Amazonas as a subsidy to the development of activities in Physical Education as a way to promote interculturality and sustainability in the school environment. The research is characterized as a qualitative approach, with analytical descriptive purpose based on bibliographic, documental and research-action. This study was developed in neighborhoods of the city of São Gabriel da Cachoeira and in the premises of the Instituto Federal de Educação, Ciência e Tecnologia do Amazonas, Campus São Gabriel da Cachoeira - IFAM/SGC. The research involved 82 indigenous students from IFAM/SGC and 41 adult participants also living in the city of São Gabriel Cachoeira of both sexes. According to the results obtained, it was possible to observe the relations of balance and sustainability with the place where they live, which can break vicious circles of a consumerist society that does not consider the protagonism of indigenous peoples and their millenary knowledge in educational processes. 43 different types of games, toys and games from 8 indigenous ethnic groups (Tukano, Piratapuia, Baniwa, Baré, Cubeo, Tariano, Potiguara and Dessano) were identified and registered, which were grouped into seven categories, namely: (1) physical contingency games; (2) motor sensory exercise games; (3) social contingency games; (4) construction games; (5) turbulent games; (6) symbolic/account games; (7) rule games. The vast majority of games and jokes involved the motor, cultural and social relations dimensions and are applicable in the teaching of school Physical Education. These knowledge apparatuses amplify diverse forms of discussions in the field of sustainability, interculturality, globalization, valuing ethnic diversity and strengthening identities that can be worked on before, during and after school, as well as providing for adaptations within and outside the school space. This research will provide conditions to propose the construction of new paths in which the present dialogues with the past, making it relevant to consider the contributions and visions of these peoples for sustainable development, as well as for the management and conservation of natural resources.
Keywords: Indígenas - Educação; Escolas - Exercícios e jogos; OUTROS; Povos Indígenas; Educação Física Escolar; Interculturalidade; Sustentabilidade; Educação física